Death and dying sourcebook : basic consumer health information about end-of-life care and related perspectives and ethical issues, including end-of-life symptoms and treatments, pain management, quality-of-life concerns, the use of life support, patients' rights and privacy issues, advance directives, physician-assisted suicide, care giving, organ and tissue donation, funeral arrangements, and grief, along with statistical data, information about the leading causes of death, a glossary, and directories of support groups and other resources. - Omnigraphics, Inc. (Detroit, MI : Omnigraphics, 2016)
"Provides basic consumer health information about management of end-of-life symptoms, caregiving and facility evaluation, and legal and economic issues associated with end-of-life. Includes index, glossary of related terms, and other resources"--
pt. X. Additional help and information : -- Glossary of end-of-life terms -- Support groups for end-of-life issues -- Resources for information about death and dying.
Includes bibliographical references and index.
Keywords: Death; Terminal care; Palliative treatment; Alzheimer's disease -- Patients -- Care; Alzheimer's disease -- Palliative treatment; Cancer -- Palliative treatment; AIDS (Disease) -- Palliative treatment; HIV infections -- Palliative treatment; Sudden infant death syndrome; Palliative treatment -- Moral and ethical aspects; Terminal care -- Moral and ethical aspects; Life support systems (Critical care); Donation of organs, tissues, etc; Assisted suicide; Hospice care; Long-term care of the sick; Long-term care facilities; Nursing homes; Caregivers; Caregivers -- Decision making; Terminally ill children; Fetal death; Infants -- Death; Children and death; Grief; Bereavement; Cremation; Funeral rites and ceremonies; Death -- Economic aspects; Death -- Legal status, laws, etc; Patients -- Legal status, laws, etc